A novel low-risk germline variant in the SH2 domain of the SRC gene affects multiple pathways in familial colorectal cancer - Skopelitou, Diamanto; Miao, Beiping; Srivastava, Aayushi; Kumar, Abhishek; Kuświk, Magdalena; Dymerska, Dagmara; Paramasivam, Nagarajan; Schlesner, Matthias; Lubiński, Jan; Hemminki, Kari; Försti, Asta; Bandapalli, Obul Reddy (Journal of Personalized Medicine, 2021)
Colorectal cancer (CRC) shows one of the largest proportions of familial cases among different malignancies, but only 5-10% of all CRC cases are linked to mutations in established predisposition genes. Thus, familial CRC constitutes a promising target for the identification of novel, high- to moderate-penetrance germline variants underlying cancer susceptibility by next generation sequencing. In this study, we performed whole genome sequencing on three members of a family with CRC aggregation. Subsequent integrative in silico analysis using our in-house developed variant prioritization pipeline resulted in the identification of a novel germline missense variant in the SRC gene (V177M), a proto-oncogene highly upregulated in CRC. Functional validation experiments in HT-29 cells showed that introduction of SRCV177M resulted in increased cell proliferation and enhanced protein expression of phospho-SRC (Y419), a potential marker for SRC activity. Upregulation of paxillin, β-Catenin, and STAT3 mRNA levels, increased levels of phospho-ERK, CREB, and CCND1 proteins and downregulation of the tumor suppressor p53 further proposed the activation of several pathways due to the SRCV177M variant. The findings of our pedigree-based study contribute to the exploration of the genetic background of familial CRC and bring insights into the molecular basis of upregulated SRC activity and downstream pathways in colorectal carcinogenesis.
Gesehen am 26.05.2021